XRDUA: crystalline phase distribution maps by two‐dimensional scanning and tomographic (micro) X‐ray powder diffraction. (1st June 2014) - De Nolf, Wout; Vanmeert, Frederik; Janssens, Koen
<x xml:space="preserve">Abstract</x> Imaging of crystalline phase distributions in heterogeneous materials, either plane projected or in virtual cross sections of the object under investigation, can be achieved by scanning X‐ray powder diffraction employing X‐ray micro beams and X‐ray‐sensitive area detectors. Software exists to convert the two‐dimensional powder diffraction patterns that are recorded by these detectors to one‐dimensional diffractograms, which may be analysed by the broad variety of powder diffraction software developed by the crystallography community. However, employing these tools for the construction of crystalline phase distribution maps proves to be very difficult, especially when employing micro‐focused X‐ray beams, as most diffraction software tools have mainly been developed having structure solution in mind and are not suitable for phase imaging purposes. XRDUA has been developed to facilitate the execution of the complete sequence of data reduction and interpretation steps required to convert large sequences of powder diffraction patterns into a limited set of crystalline phase maps in an integrated fashion.